101Pre-onset sun exposure significantly associated with risk of primary biliary cirrhosis. (2nd September 2021) - French, Janine; Simpson-Yap, Steve; Ng, Justin; Angus, Peter; van der Mei, Ingrid; Gow, Paul
Abstract: Background: Primary biliary cholangitis (PBC) is an autoimmune destructive condition of the gall bladder, with environmental factors like sun exposure implicated in its aetiology, similar to multiple sclerosis. Using a case-control study design, we assessed sun exposure across the life course prior to PBC diagnosis between PBC cases and age/sex-matched healthy controls. Methods: Cases with definite/probable PBC were recruited, these having been identified from a PBC prevalence study. Age/sex matched controls were recruited from the electoral roll or at the Austin Hospital. Pre-onset sun exposure behaviours were queried at baseline by questionnaire and life calendar, this combined with ambient UVR data to estimate total UVR load. Relationships with case status were assessed using conditional logistic regression. Results: 200 cases and 200 age/sex-matched controls were recruited. 91% of the cases were female and the mean age was 63.6 years. Increasing sun exposure was associated with significantly lower odds of being a case, robust to adjustment for birthplace, education and smoking, the strongest associations seen for summer exposure in 6-10yo (OR = 0.39), 11-16yo (OR = 0.44), and 16-20yo (OR = 0.47). Similar results were seen for ambient UVR. Conclusions: Higher pre-onset sun exposure and UVR load were associated with a decreased risk of primary biliary cholangitis. This is the first study that has examined the environmental risk factors of sun exposure and UV radiation with regard to PBC. Key messages: In line with the observation of a significant latitudinal gradient in PBC prevalence, this work shows that pre-onset sun exposure is significantly lower among PBC cases compared to matched controls, suggesting sun exposure has an aetiological relationship with PBC risk.